Pengaruh Strategi Pembelajaran Critical Incident terhadap Hasil Belajar Bahasa Indonesia Murid Kelas V SD Inpres Bangkala II - Husnul Khotimah Rustam; Nur Rahmatan Mursalin (IAI DDI POLEWALI MANDAR, 2023)
The main purpose of this study is to empirically determine the effectiveness of the application of critical incident learning strategies on learning outcomes Indonesian SD Inpres Bangkala II. From this goal, the research method that is practiced is the experimental method. Researchers used the pre-post test as a data collection device. The method is carried out on students (i) fifth grade. The results of this study show that there is an increase in learning outcomes of Indonesian subjects using critical incident learning strategy interventions in students (i). The implications of this research can also be applied to students (i) of early childhood kindergarten age by providing interactive activities so as to hone critical thinking skills. Students (i) learn to think critically so as to increase achievement, curiosity, Indonesian language literacy, to be able to solve problems in everyday life. Students(i) are also fluent in communicating clearly and intensively with both teachers and peers